2021
DOI: 10.3390/coatings11111325
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition and Magnetoelectric Effect in 2D Ferromagnetic Films on a Ferroelectric Substrate

Abstract: In this paper, we investigate the behavior of 2D ferromagnetic (FM) films on a ferroelectric (FE) substrate with a periodic structure. The two-dimensional Frenkel–Kontorova (FK) potential simulates the substrate effect on the film. The substrate potential corresponds to a cubic crystal lattice. The Ising model and the Wolf cluster algorithm are used to describe the magnetic behavior of a FM film. The effect of an electric field on a FE substrate leads to its deformation, which is uniform and manifests itself i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…U 2 x , z = A 0 z , σ 0 + A 2 z , σ 0 cos 4πx (10) This expression also boils down to the Frenkel-Kontorova potential. The potential U 2 (x , z ) has a period of two times less than that for the substrate atoms.…”
Section: 𝑈(𝑥′ 𝑧′mentioning
confidence: 75%
See 2 more Smart Citations
“…U 2 x , z = A 0 z , σ 0 + A 2 z , σ 0 cos 4πx (10) This expression also boils down to the Frenkel-Kontorova potential. The potential U 2 (x , z ) has a period of two times less than that for the substrate atoms.…”
Section: 𝑈(𝑥′ 𝑧′mentioning
confidence: 75%
“…The potential of the atom's chain is approximated by the formula with two terms at the point 𝜎 0 . 𝑈 2 (𝑥′, 𝑧′) = 𝐴 0 (𝑧′, 𝜎 0 ) + 𝐴 2 (𝑧′, 𝜎 0 )cos(4π𝑥′) (10) This expression also boils down to the Frenkel-Kontorova potential. The potential 𝑈 2 (𝑥′, 𝑧′) has a period of two times less than that for the substrate atoms.…”
Section: 𝑈(𝑥′ 𝑧′mentioning
confidence: 81%
See 1 more Smart Citation
“…For instance, a large variety of molecular and biomolecular ferroelectrics can be used as the spin transport medium in OMFJs. Extensively used magnetic films may be replaced by other magnetic compounds with high polarization in spin [25,[80][81][82][83], new magnetic constituents such as 2D van der Waals materials [169][170][171][172][173][174][175], or 2D networks of organic and metal-organic magnets on surfaces [110][111][112][176][177][178][179][180][181][182][183], metal-organic frameworks [20,21], heterostructures [110,111,[184][185][186] and organic spinterfaces [13,49,51,[90][91][92]163,187] as electrodes to improve the spin injection and/or the functionality of OMFJs. A few recent successful examples already include some of these new alternative types of electrodes for photovoltaic [188], capacitive [189] and spin-crossover [190] devices.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of the exchange integral for the spin–spin interaction on distance has a main influence on the change in magnetic properties. Studies of the substrate deformations effect on the magnetic properties of single-layer 2D films on a non-magnetic substrate [ 11 , 12 , 13 ] have shown that uniform substrate deformations can lead to non-uniform film deformations at the free ends of the film. Islands with increased concentration of atoms are formed in the film when the substrate is compressed.…”
Section: Introductionmentioning
confidence: 99%